2013
DOI: 10.1186/1472-6963-13-113
|View full text |Cite
|
Sign up to set email alerts
|

Existence and functionality of emergency obstetric care services at district level in Kenya: theoretical coverage versus reality

Abstract: BackgroundThe knowledge on emergency obstetric care (EmOC) is limited in Kenya, where only partial data from sub-national studies exist. The EmOC process indicators have also not been integrated into routine health management information system to monitor progress in safe motherhood interventions both at national and lower levels of the health system. In a country with a high maternal mortality burden, the implication is that decision makers are unaware of the extent of need for life-saving care and, therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 24 publications
4
67
0
Order By: Relevance
“…A number of surveys have shown that the majority of health-care facilities in low-and middleincome settings, although designated to provide either basic or comprehensive EmONC, may be unable to do so [26,27]. In many cases, structures are in place, and equipment and consumables were noted to be available, but the staff reported that they lacked competency and skills and were therefore unable to provide all the signal functions of EmONC and essential NC [21,22,26].…”
Section: Emergency Obstetric Carementioning
confidence: 94%
“…A number of surveys have shown that the majority of health-care facilities in low-and middleincome settings, although designated to provide either basic or comprehensive EmONC, may be unable to do so [26,27]. In many cases, structures are in place, and equipment and consumables were noted to be available, but the staff reported that they lacked competency and skills and were therefore unable to provide all the signal functions of EmONC and essential NC [21,22,26].…”
Section: Emergency Obstetric Carementioning
confidence: 94%
“…The long travel times greatly reduce their chances of surviving an obstetric emergency: this is because longer travel times, as pointed out by Echoka et al . (), may lead to women arriving in such severe conditions that it may be impossible to save their lives.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Echoka et al . (), equity can be measured in terms of the spatial distribution and accessibility of health facilities, which in turns dictates their level of use. Our study showed a non‐uniform distribution of health facilities, hence signifying unequitable access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations